Number Sense Siswa dalam Pemecahan Masalah Matematika Ditinjau dari Gaya Kognitif Verbalizer - Ciptianingsari Ayu Vitantri; Selvira Hadi Miftahurrohmah; Tomy Syafrudin (JRPM (Jurnal Review Pembelajaran Matematika), 2020)
This study aims to describe the student's number sense in solving math problems in terms of the verbalizer's cognitive style. This is qualitative research, with research instruments are cognitive style tests, problem-solving tests, and interview guides. The results showed that (1) at the reading and thinking stage, the students' could identify questions and explain mathematical terms and numbers in the questions appropriately, (2) at the exploring and planning stage, the students' could determine the steps to take from solving the problem through an example, (3) at the phase of choosing a strategy, the students' could find the relationship between the numbers in the matter and state the appropriate formula to solve the problem, (4) in the search for answers, the students' could perform mental calculations and estimate calculations in the form of root prediction and rounding of numbers with accuracy, and (5) at the reflecting and expanding stage, the students wrote the final result of the answer in detail and wrote the conclusions on each calculation result obtained, and corrected again the results of his work.